An experiment on information presentation and investor mutual fund selection - Billie Anderson; Nathan Mauck; Leigh Salzsieder (Cogent Economics & Finance, 2023)
Our experiments evaluate the role of information presentation in reducing violations of the Law of One Price in individual investor selection of index mutual funds. The results indicate that most individuals fail to minimize fees. However, individuals allocate nearly 27% (43%) more of their investment dollars to the lowest fee index mutual fund when receiving fee information in the form of a table compared to a graph presentation (in ten-year rather than one-year form). Overall, a simple change from table to graph fee presentation results in a statistically and economically significant reduction in the fees paid by investors.
Keywords: C91; D03; D14; G11; G23; 330; behavioral finance; data visualization; diversification bias; Mutual funds; S&P index funds